A case of primary extraosseous penile osteosarcoma and review of the literature - Shringarpure, Sanish S. (Medknow Publications & Media Pvt Ltd, 2012)
Primary extraskeletal osteosarcoma of the penis (ESO) is a very rare condition. As per our knowledge, this is the seventh reported case in the world literature. We report a case of primary ESO of the penis in a young male, which was treated with surgery and adjuvant chemotherapy. This case is presented for its rarity and the scarcity in the literature regarding its treatment and prognosis.